2020
DOI: 10.1080/26895293.2020.1718777
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract of Erythrina senegalensis leaves (MEES) ameliorates Plasmodium berghei-ANKA 65-parasitised aberrations in mice

Abstract: The aim of this research was to investigate the phytochemical composition and antimalarial effects of the methanol extract of Erythrina senegalensis leaves (MEES) and its ameliorative effects on some haematological and biochemical alterations in Plasmodium berghei-infected mice. Thirty Swiss mice, 18-22 grams were placed in 6 groups of 5 mice. Group 1 served as normal control. Groups 2-6 were infected with P. berghei. Group 2 was untreated while group 3 was treated with 5 mg/kg body weight of chloroquine. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(44 reference statements)
9
1
0
Order By: Relevance
“…The increased activities of the aminotransferases (AST, ALT) and alkaline phosphatase could be as a result of hepatocellular injury (Gowda et al, 2009) while the increased hyperbilirubinemia could be due to parenchymal liver cell damage and biliary obstruction induced by the liver schizonts of malaria parasite (Limdi and Hyde, 2003;Hoekstra et al, 2013). This finding is in agreement with previous studies (Enechi et al, 2021;Iyiola, 2020;Joshua et al, 2020) which reported increased liver enzyme activities and hyperbilirubinemia in mice infected with Plasmodium berghei. The reduction of the elevated AST, ALT and ALP showed that the extract was effective in reversing the hepatocellular damage caused by the Plasmodium parasite.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The increased activities of the aminotransferases (AST, ALT) and alkaline phosphatase could be as a result of hepatocellular injury (Gowda et al, 2009) while the increased hyperbilirubinemia could be due to parenchymal liver cell damage and biliary obstruction induced by the liver schizonts of malaria parasite (Limdi and Hyde, 2003;Hoekstra et al, 2013). This finding is in agreement with previous studies (Enechi et al, 2021;Iyiola, 2020;Joshua et al, 2020) which reported increased liver enzyme activities and hyperbilirubinemia in mice infected with Plasmodium berghei. The reduction of the elevated AST, ALT and ALP showed that the extract was effective in reversing the hepatocellular damage caused by the Plasmodium parasite.…”
Section: Discussionsupporting
confidence: 94%
“…The reduction in plasma concentration of bilirubin of mice infected with Plasmodium berghei and treated with the extract shows that the extract reversed liver cell damage and restored liver cell function. This is consistent with the report of Joshua et al (2020) which showed that E. sengalensis extract lowered total bilirubin concentration in Plasmodium berghei infected mice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study shows evidence of dyslipidaemia in P. berghei infection. This is in conformity with the previous studies that demonstrated increased TC and LDL-c in human and rodent malaria (Ngou-Milama et al, 1995;Krishna et al, 2009;Jacob, 2014) and rodents (Joshua et al, 2020). Treatments with both chloroquine and the extract lowered TC and LDL-c in P. berghei-infected mice, suggesting the efficiency of the extract in mitigating malaria-induced dyslipidaemia.…”
Section: Discussionsupporting
confidence: 92%